SERVICE QUALITY ANALYSIS OF CAMPUS-BASED MOTORCYCLE TAXI (GOPUS): AN INTEGRATED SERVQUAL–IPA–PGCV APPROACH - Dinda Renata Cecilia; Rina Filia Sari; Rini Halila Nasution (Pena Cendekia Insani, 2025)
This study evaluates the service quality of GOPUS, an informal,WhatsApp-based campus ride-hailing service at UINSU, Indonesia. Using a quantitative approach, data were collected from 100 student respondents via Likert-scale questionnaires assessing expectations andperceptions across five SERVQUAL dimensions. After validity and reliability screening, 16 items remained for analysis. The SERVQUALgap analysis, Importance-Performance Analysis (IPA), and PotentialGain in Customer Value (PGCV) index were applied to identify improvement priorities. Results reveal a negative service gap across keyattributes, with five indicators falling into IPA Quadrant I (ConcentrateHere). PGCV prioritizes driver service satisfaction (P GCV = 5.95) andtraining (P GCV = 3.75) for immediate intervention. The findings provide actionable recommendations for enhancing operational standards,safety, and user satisfaction in informal campus transport systems.